Capital Structure Priority Effects in Durations, Stock-Bond Comovements, and Factor Pricing Models - Choi, Jaewon; Richardson, Matthew; Whitelaw, Robert F (The Review of Asset Pricing Studies, 2022)
We show theoretically and empirically that the durations of corporate securities are monotonically related to their capital structure priority, with equity often having a negative duration. The magnitude of this effect increases with firm leverage. We use these insights to challenge existing results on stock-bond comovements and factor pricing. For example, though overlooked, higher leverage and lower priority reduce the correlation between corporate security and government bond returns, and these variables explain time-series and cross-sectional variation in correlations; traditional market model regressions significantly understate corporate bond betas; and regressions on standard term and default factors dramatically overstate interest rate and default risk. (JEL G12, G13)